SRATEGI INDONESIA DALAM MENGATASI PENYELUNDUPAN NARKOTIKA LINTAS BATAS TAHUN 2013-2017 (STUDI KASUS: KEPULAUAN RIAU) - Sri Rahayu Ningsih; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This paper is a study of the security strategy that explains about the smuggling of narcotics. This study discusses the strategy of Indonesia in addressing cross-border drug smuggling in Riau Islands in 2013-2017. The purpose of this study is to determine what strategies undertaken by Indonesia in addressing cross-border drug smuggling in the Riau Islands. Riau Islands is one of the provinces in Indonesia bordering with neighboring countries, the location is prone to make frequent occurrence Smuggling in Riau Islands, one of which is smuggling narcotics. Narcotics smuggling itself is a crime that is crimes committed by crossing national borders.This is qualitative research which used descriptive methods, and collecting datas from interview, books, journals, articles, mass media, official ublications and relevant websites. This paper used the neoliberalism perspective written by Kenneth Waltz, analysis unit nation-state written by Mohtar Mas’oed and the theory is Strategy written by John Lovell.The result of this research is that Indonesia's strategy in dealing with narcotics smuggling is to perform actions that optimize the role of BNN and external actions which by cooperation with Malaysia.Keywords: Narcotic, Smuggling, Riau Island, Security Strategy.